Data-Driven Augmented Reality for Scout Password Recognition in Interactive Learning Environment - M. Soekarno, Putra; Nurul Adha Oktarini, Saputri; Rezania Agramanisti, Azdy; Nirwana, . (INTI International University, 2024)
Scout password is an essential component of scout science, used for communication through secret codes. Learning scout passwords has traditionally relied on conventional methods, where coaches provide material and exercises during weekly meetings. Due to infrequent practice opportunities, this approach often limits students' ability to engage deeply with the material. To address these challenges, this research introduces a data-driven augmented reality (AR) application designed to enhance the learning experience by making scout password recognition more interactive and accessible. The proposed tool leverages AR technology to provide real-time visualization of movements and auditory cues, creating an immersive and engaging learning environment. By integrating data-driven insights into the AR application, the learning process is tailored to individual student needs, ensuring effective understanding and retention of scout codes. The development process follows the Multimedia Life Cycle methodology, providing a structured and iterative approach to creating a user-friendly and impactful application. This innovative AR-based tool aims to transform traditional scout learning methods, offering students a more dynamic and interactive way to master scout password communication while addressing the limitations of conventional teaching practices.